Analysis Of Students' Mathematical Communication Ability And Problem-Solving Ability On The System Of Linear Equations With Two Variables (SPLDV) In Grade VIII - Christin Geovani Purba; Samuel Juliardi Sinaga; Tutiarny Naibaho (STABN RADEN WIJAYA WONOGIRI, 2021)
This study aims to analyze students’ mathematical communication skills and problem-solving abilities on the topic of Systems of Linear Equations in Two Variables (SPLDV) in Grade VIII of SMP Swasta HKBP Sidorame in the Academic Year 2025/2026. The background of this research is the low level of students’ skills in communicating mathematical ideas and in solving problems related to real-life situations.This research is a descriptive qualitative study with 14 eighth-grade students as the subjects. The instruments used consisted of an essay test on mathematical communication skills, a problem-solving test, and interviews. The data were analyzed through validity testing, reliability testing, difficulty level, and discriminating power, and then presented descriptively based on the established indicators.The results of the study indicate that students’ mathematical communication skills fall into the medium category, with 14.29% of students in the high category, 57.14% in the medium category, and 28.57% in the low category. In terms of problem-solving skills, 21.43% of students were in the high category, 64.29% in the medium category, and 14.28% in the low category. Students were relatively able to express mathematical ideas in both visual and written forms and to develop a solution plan, but they still experienced difficulties in interpreting ideas and reviewing their answers. The study concludes that students’ mathematical communication and problem-solving skills are in the medium category, thus more varied learning strategies are needed to improve these two abilities.